GEOGRAPHICAL ANALYSIS OF WATER RESOURCES IN MORADABAD DISTRICT - Singh, Mukesh; Kumar, Pradeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Water is an important resource among natural resources and it is a basic necessity for all living beings. Moradabad district is situated between 28 degrees 06’ north latitude to 28 degrees 40’ and 78 degrees 04’ to 78 degrees 27’ east longitude, whose area is 2208 square kilometers. The total population is 31.26 lakh persons and the population density is 14.15 persons per square kilometer. Availability of water resources in Moradabad district is present in the form of rivers, canals, streams, lakes, ponds and subsoil water. Annual rainfall is 110 cm and depth of subsoil water level is 8.00 m. Length of canals is 511 km and 175 ponds and lakes are situated. In Moradabad district, water resources are used as per requirement in various works in which consumptive use is more visible. Use of water in various works is increasing rapidly. Keeping in view the future water demand, water conservation is necessary.